Protoptype Pengairan Sawah dan Monitoring Kualitas PH Tanah Berbasis IOT - Dian Megah Sari; Jumardi Jumardi; Nurdina Rasjid (Infotek: Jurnal Informatika dan Teknologi, 2022)
Rice is a food crop commodity that produces rice which plays an important role in the economic life of Indonesia. Rice as a staple food is very difficult to replace by other staples. This study aims to determine the results of the design of the internet-based monitoring system for rice field irrigation and to determine the results of monitoring soil pH with Thinger.io. The tools used in the design of this system are Node MCU ESP8266, Ultrasonic Sensor HC-SR04, Soil pH Sensor, Servo Motor (MicroServo 9G – SG90), UTP Cable. Soil pH sensor can send soil acidity level data to NodeMCU and send data to thingger to display results, while ultrasonic sensor can read elevation value on surface if water level (11 cm) then servo will receive signal to open and when water level height value ( 6 cm) then the servo will receive a signal to close, the last process is to send data to the web server or thingger.io. The results of the pH test are that with a pH value equal to 7 then it is suitable for planting rice seeds and if the pH value is below 7 then it is not suitable for planting rice and dolomid lime will be added to neutralize the acidity level in the soil of paddy fields. The tests carried out are using the BlackBox method and the results of this test are the system runs as expected